Is speed reserve related to critical speed and anaerobic distance capacity in swimming? - Dalamitros, A. A.; Fernandes, R. J.; Toubekis, A. G.; Manou, V.; Loupos, D.; Kellis, S. (The Journal of Strength and Conditioning Research, 2015)
This study examines the relationship between speed reserve (SRes), critical swimming speed (CSS), and anaerobic distance capacity (ADC) and their efficacy in determining training adaptations. Swimmers with previous competitive experience participated in an 8-week aerobic training program (experimental group: E; n = 15, age: 22.29 ± 0.95 years) and a control group refrained from training during the same period (C; n = 6, age: 22.25 ± 2.22 years). Speed reserve was determined before and after training from the speed difference between the 50 and 400 m maximum tests. Both CSS and ADC were calculated using 2 different combinations of distances (50 and 400 m: CSS2/ADC2; 50, 100, and 400 m: CSS3/ADC3) by applying the distance-time linear regression model. CSS2 and CSS3 of the E group showed a negative correlation, whereas ADC2 and ADC3 showed a positive correlation, with SRes before and after the training period (r = -0.66, r = 0.88, p = 0.05). CSS2 and CSS3 increased by 5.5 ± 3.2 and 6.0 ± 3.2%, whereas ADC2, ADC3, and SRes decreased by 12.0 ± 9.4, 9.0 ± 11.2, and 8.1 ± 8.4% with the training program (p = 0.05). These findings suggest that SRes, as calculated from distances of 50 and 400 m, shows strong relationships with CSS and ADC and may be used as an indicator of training-induced changes. This information is expected to facilitate training control and evaluation in a day-to-day basis.